Efficacy of a Probiotic‐Prebiotic Supplement on Incidence of Diarrhea in a Dog Shelter: A Randomized, Double‐Blind, Placebo‐Controlled Trial. (10th February 2017) - Rose, L.; Rose, J.; Gosling, S.; Holmes, M.
Abstract : Background: Diarrhea is the most frequent morbidity affecting kenneled dogs in animal shelters. Diarrhea impacts animal welfare and the finances of the shelter as they must treat, clean, and house affected animals until recovered. Hypothesis/Objectives: Supplementing dogs entering an animal shelter with a probiotic‐prebiotic, known as a synbiotic, will decrease the incidence of diarrhea. Animals: Seven hundred and seventy‐three dogs entering an animal shelter in the United Kingdom. Methods: A prospective double‐blind, randomized, placebo‐controlled trial. Results: Statistical difference was found between the groups across 3 measures of diarrhea incidence. First, the mean percentage of scored days per dog that were scored as diarrhea throughout their stay was 2.0% in the synbiotic group and 3.2% in the placebo group ( P = .0022). Second, the occurrence of diarrhea within the first 14 days' stay was 18.8% in the synbiotic product group and 27.2% in the placebo group ( P = .0008). Third, the occurrence of ≥2 consecutive days of diarrhea within the first 14 days' stay was 4.6% in the synbiotic product group and 8.0% in the placebo group ( P = .0300). Conclusions and clinical importance: Supplementing healthy dogs entering an animal shelter with a synbiotic supplement significantly decreased the incidence of diarrhea in this trial. Animal shelters can use synbiotic supplements to improve animal welfare and decrease costs involved in cleaning and housing animals as well as potentially decreasing veterinary intervention.